Analisis Herding Behavior Sebelum Dan Sesudah Penghapusan Kode Broker Di Bursa Efek Indonesia - Cahyono, Aji Wikan; Robiyanto, Robiyanto; Harijono, Harijono (Magister Manajemen STIE Bank BPD Jateng, 2024)
This research was conducted to see if there was any herding behavior in stock trading in Indonesia, especially the LQ45 index constituents, which were affected by the effect of the removal of the broker code by the Indonesian Stock Exchange which began on December 6, 2021. The period used in this study was the period before the removal of the broker code, namely June 15, 2020 to December 5, 2021 and the period after the removal of the broker code, namely December 6, 2021 to June 30, 2023. The method used in this study is the approach method by Chang et al. (2000) namely CSAD (Cross Sectional Absolute Standard Deviation) to detect indications of herding behavior. The results of this study indicate that there was no herding behavior on the LQ45 trading stock index either before or after the removal of the broker code. This means that investors act rationally whether the broker code exists or not